DOSE-DEPENDENT CHRONIC TOXICITY SCREENING OF HINOKITIOL IN ZEBRAFISHES: BEHAVIORAL AND HISTOLOGICAL APPROACH - KRISHNAPRIYA MADHU VARIER; SUMATHI THANGARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Parkinson’s disease (PD) is categorized as a movement disorder symptomized by weakening the motor skills of the patients. The root cause of the disease is the neurodegenerative dopaminergic loss in the substantia nigra of the patient’s brain. This havoc disease majorly affects the people above the age of 60 years. Moreover, PD incidences strike almost 70% of the neurological disorders of the aged population worldwide. There are no perfect curative drugs in the medical world for the disease. Since the past few decades, several plant secondary compounds were in preclinical trials to treat this disease. Hinokitiol (HIN), a monoterpenoid from the heartwood of cupressaceous plants, is widely used in hair tonics, toothpaste, cosmetics, and food as an antimicrobial agent. It is well reported as an anti-stroke agent as well. Methods: In the present study, the dose-dependent (5, 10, 15, 20, and 25 mg/kg) chronic toxicity of HIN was studied for 28 days using zebrafishes. The toxicity was analyzed in vital organs such as brain, liver, kidney, spleen, heart, and blood count followed by behavioral toxicity to target the drug against parkinsonism. Results: The study revealed that the higher doses of 20 and 25 mg/kg HIN treatment were toxic to the fish brain, spleen, as well as cardiomyocytes. It showed a variation in blood count as well at 10 mg/kg dose itself. Conclusion: Hence, the study revealed the protective efficacy of the HIN at its therapeutic dosage of 5 mg/kg as a neuroprotective drug, with minimal vital organ toxicities.